Functional adaptation of cortical interneurons to attenuated activity is subtype-specific - Karayannis, Theofanis; De Marco Garcia, Natalia V.; Fishell, Gordon J. (Frontiers in Neural Circuits, 2012)
Functional neuronal homeostasis has been studied in a variety of model systems and contexts. Many studies have shown that there are a number of changes that can be activated within individual cells or networks in order to compensate for perturbations or changes in levels of activity. Dissociating the cell autonomous from the network-mediated events has been complicated due to the difficulty of sparsely targeting specific populations of neurons in vivo. Here, we make use of a recent in vivo approach we developed that allows for the sparse labeling and manipulation of activity within superficial CGE-derived GABAergic interneurons. Expression of the inward rectifying potassium channel Kir2.1 cell-autonomously reduced neuronal activity and lead to specific developmental changes in their intrinsic electrophysiological properties and the synaptic input they received. In contrast to previous studies on homeostatic scaling of pyramidal cells, we did not detect any of the typically observed compensatory mechanisms in these interneurons. Rather, we instead saw a specific alteration of the kinetics of excitatory synaptic events within the reelin-expressing subpopulation of interneurons. These results provide the first in vivo observations for the capacity of interneurons to cell-autonomously regulate their excitability.